FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN NON KEUANGAN - Tita, Merry Susanti (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study was to examine the effect of profitability, liquidity, market to book value, debt to equity ratio, firm size, collateralizable asset, and operating cash flow on dividend policy of non financial company that listed in Indonesia Stock Exchange for the period 2016-2018. This research used 125 of non financial company that was selected using purposive sampling method. This research used secondary data take from www.idx.co.id website and processed by Eviews 10. The results of this study indicate that profitability have negative and significant influence effect on dividend policy. Debt to equity ratio and collateralizable asset have positive and significant effect on dividend policy, while liquidity, market to book value, firm size, and operating cash flow have no significant effect on dividend policy.